2013
DOI: 10.1021/pr4005629
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of Protein Targets: Proteomic Characterization of Bacterial Spore Outer Layers

Abstract: Bacillus cereus, responsible for food poisoning, and Clostridium difficile, the causative agent of Clostridium difficile-associated diarrhea (CDAD), are both spore-forming pathogens involved in food spoilage, food intoxication, and other infections in humans and animals. The proteinaceous coat and the exosporium layers from spores are important for their resistance and pathogenicity characteristics. The exosporium additionally provides an ability to adhere to surfaces eventually leading to spore survival in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 83 publications
(147 reference statements)
3
85
0
Order By: Relevance
“…exosporium proteins, except for the presence of collagen-like proteins (187). However, the lack of B. cereus family exosporium homologs does not rule out the existence of C. difficile exosporium structures, since genomic analyses of known exosporium producers outside the B. cereus family suggest that exosporium proteins differ markedly in various species.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…exosporium proteins, except for the presence of collagen-like proteins (187). However, the lack of B. cereus family exosporium homologs does not rule out the existence of C. difficile exosporium structures, since genomic analyses of known exosporium producers outside the B. cereus family suggest that exosporium proteins differ markedly in various species.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…difficile spore morphology resembles that of other sporeforming bacteria; however, the protein composition of the outer layers (i.e., the spore coat and exosporium layer) differs greatly from that of other Gram-positive bacteria (13,14). The composition of the spore coat has been described recently (7); fewer than 25% of the spore proteins and several spore coat proteins have been functionally characterized (8,9). Transmission electron microscopy (TEM) reveals the presence of typical laminations (i.e., lamellae) (6,(10)(11)(12) in the spore coat of other spore-forming bacteria (13).…”
mentioning
confidence: 96%
“…The mutant contains a chromosomal mutation that replaces the entire cotB1 and cotB2 genes with an Sp r cassette. We also constructed another mutant strain, a ⌬cotG mutant, as a negative control, in which the Sp r cassette replaces the gene encoding another spore coat protein Cot␥ (31) (formerly known as an exosporium protein ExsB [32]; however, recent studies showed that most of this protein is located in the spore coat [31,33]). These mutant strains grew as fast and formed spores at the same rate as the wild type in mR2A medium with 100 g ml Ϫ1 silicate (data not shown), suggesting that the cotB1B2 and cotG disruption did not affect vegetative growth or spore formation.…”
Section: Resultsmentioning
confidence: 99%